2014
DOI: 10.1002/ardp.201300379
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Substituted N‐[3‐(1H‐Pyrrol‐1‐yl)methyl]‐1,2,5,6‐tetrahydropyridin‐1‐yl]benzamide/benzene Sulfonamides as Anti‐Inflammatory Agents

Abstract: The pharmacological activities of tetrahydropyridine (THP) derivatives are dependent on the substituent ring moiety. In this study, we investigate the anti-inflammatory activities of 12 newly synthesized substituted N-[3-(1H-pyrrol-1-yl)methyl]-1,2,5,6-tetrahydrobenzamide/benzene sulfonamides (9a–l) in murine BV-2 microglial cells. All compounds were initially screened for attenuation of nitric oxide (NO) production in lipopolysaccharide (LPS) (1 μg/mL)-activated microglial cells. The data show that only SO2-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In recent times, there has been an increase in studies regarding the substances containing sulfonamide fragment because of their potential applications such as for coordination chemistry 18 , medicinal chemistry 19 , catalyst chemistry 20 , chemical luminescence 21 and analytical chemistry fields 22 . On the other hand, sulfonamide compounds are known to contain inherent pharmacological properties such as antimicrobial 23 , anti-inflammatory 24 , anti-viral 25 , anti-proliferative 26 , angiogenesis 27 and enzyme inhibitory (carbonic anhydrase) activities 28 . Therefore, based on these findings, sulfonamide compounds were synthesized by the reaction of sulfonamide fragments; N-(2-amino-5-benzoylphenyl)-4-nitrobenzenesulfonamide hydrochloride (1), N-(quinolin-8-yl)-4-nitro-benzenesulfonamide hydrochloride (2), N-(pyridine-2-ylmethyl)-4-nitro-benzenesulfonamide hydrochloride (3) with3,4-diaminobenzophenone, 8-aminoquinoline or 2-picoylamine and 4-nitrobenzensulfonyl chloride, respectively and we tested the effects compounds on cell viability, pro-apoptotic gene expression and of p38/ERK activation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there has been an increase in studies regarding the substances containing sulfonamide fragment because of their potential applications such as for coordination chemistry 18 , medicinal chemistry 19 , catalyst chemistry 20 , chemical luminescence 21 and analytical chemistry fields 22 . On the other hand, sulfonamide compounds are known to contain inherent pharmacological properties such as antimicrobial 23 , anti-inflammatory 24 , anti-viral 25 , anti-proliferative 26 , angiogenesis 27 and enzyme inhibitory (carbonic anhydrase) activities 28 . Therefore, based on these findings, sulfonamide compounds were synthesized by the reaction of sulfonamide fragments; N-(2-amino-5-benzoylphenyl)-4-nitrobenzenesulfonamide hydrochloride (1), N-(quinolin-8-yl)-4-nitro-benzenesulfonamide hydrochloride (2), N-(pyridine-2-ylmethyl)-4-nitro-benzenesulfonamide hydrochloride (3) with3,4-diaminobenzophenone, 8-aminoquinoline or 2-picoylamine and 4-nitrobenzensulfonyl chloride, respectively and we tested the effects compounds on cell viability, pro-apoptotic gene expression and of p38/ERK activation.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of THIQs has been previously described (1618) for GM-3-121, with additional information on the synthesis for GM-4-53 as follows General procedure for the synthesis of 2-amino-7-hydroxyisoquinolinium 2,4,6-trimethylbenzenesulfonate: O-mesitylene sulfonyl hydroxylamine (MSH) (3) was used to prepare the N -amino salt as an aminating agent as described (19). An ice cooled solution of 7-hydroxyisoquinoline (2.0 g, 13.78 mmol) in 30 ml of dry methylene chloride, and 15 ml of dry methanol was added drop wise to O -mesitylenesulfonylhydroxylamine (2.97 g, 13.78 mmol) in 10 ml of dry methylene chloride over 5 min with stirring.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent studies, we reported the synthesis of THIQs by N -amination of isoquinoline using hydroxylamine-O-sulfonic acid followed by ylide formation and reduction, which yielded the desired, N -substituted THIQs (1618). In this study, we evaluate the effects of these THIQs on growth parameters in TNBC cells.…”
mentioning
confidence: 99%
“…The sulfonamide moiety is a common building block in organic synthesis [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and an essential functional group in drug design. [15][16][17][18][19] Sulfonamides have a wide range of medical applications due to their anti-inflammatory, [15][16][17] antibacterial, [18][19][20][21] antimicrobial, [22][23][24] anticancer, [25][26][27][28][29][30][31] antimalarial, 32 and antipsychotic activities. 33 They have been reported to be inhibitors of DNA double-strand break repair, 34 dual angiotensin II and endothelin A receptor antagonists, 35 cyclooxygenase-2 inhibitors associated with different diseases, [36][37][38][39][40][41][42]…”
Section: Application Of Sulfonamidesmentioning
confidence: 99%